UI/UX Design of a Sales Application Using the Design Thinking Method at CV Barong Bali Jersey - BRAHMANA, IDA BAGUS GEDE NANDA BRAHMANA PUTRA; Tonyjanto, Christian; Kurniawijaya, Putu Andika (JURNAL KESEHATAN, SAINS, DAN TEKNOLOGI (JAKASAKTI), 2025)
Advances in information technology have brought significant changes to many aspects of life, including the textile industry. One business in this sector, CV Barong Bali Jersey, faced difficulties in the manual product ordering process. This led to ineffective customer service and complicated communication and the custom design ordering process. Data was collected through direct observation in the customer service area, interviews with staff and customers, and questionnaire distribution. Data analysis was performed, and the results were used to inform the design of the application's UI, business model, and features. Application prototype testing was conducted using the System Usability Scale (SUS) and the User Experience Questionnaire (UEQ). The test results showed that the application achieved an average SUS score of 80,00%, with a maximum score of 90%, indicating a high level of satisfaction. User acceptance fell within the acceptable category and approached the excellent benchmark. Furthermore, UEQ testing demonstrated positive scores across all dimensions, including system appeal, efficiency, clarity, and reliability.It can be concluded that the Design Thinking approach is highly effective in developing a sales application that meets user needs, increases user satisfaction when interacting with the system, accelerates transaction processing, and strengthens CV Barong Bali Jersey's digital competitiveness in this era of digital transformation The results of this study provide several significant contributions, namely: For CV Barong Bali Jersey: This study provides a solution in the form of a sales application that uses UI/UX design based on the Design Thinking method. This solution helps simplify the product ordering process, including ordering custom designs. The system used increases the effectiveness of customer service by being faster, clearer, and more integrated. This study helps companies adapt to the digital era, thereby increasing their business competitiveness. For Users/Customers: This application provides a better ordering experience due to its user-friendly and efficient design. With a transparent, communicative, and accessible ordering process, customers will be more satisfied with the service provided. For Academics/Researchers: This study serves as a concrete example of the application of the Design Thinking method in developing a sales application in the textile industry. In addition, this study also provides a reference for studies related to the use of usability testing (US) and user experience testing (UEQ) in the local business context. For the Development of Science and Practice: This research demonstrates that a user-based approach can produce a more effective system that meets user needs. 2. The results of this research can also serve as a basis for developing similar applications in various small and medium enterprises (SMEs) facing similar problems.